Economic Empowerment of Rural Communities through Mudharabah Scheme in Freshwater Fish Cultivation - Rusnawati; Eci Nuriantika (Al-Mubin, 2025)
The mudharabah (shahibul maal) program in freshwater fish farming is a form of sharia-based partnership that aims to improve the welfare of rural communities through a profit-sharing system. This study aims to analyze community experiences in the mudharabah (shahibul maal) program in freshwater fish farming in Lawe Pangkat Village, Southeast Aceh Regency. The method used was a qualitative ethnographic field approach through observation and semi-structured interviews with capital owners, business managers, and village officials. The results show that the mudharabah program contributed to increased income, work motivation, and community cultivation skills. The profit-sharing system agreed upon at the outset encouraged trust and active participation of managers. However, program implementation still faces obstacles such as limited capital, the risk of crop failure, and a lack of technical experience among some managers. The mudharabah program has the potential to become a model for sustainable sharia-compliant economic empowerment in the rural fisheries sector with adequate mentoring support.